ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI DESA SIDONDO 1 KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Deisye Natalia Amos. B. Lampaga (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research aimed to identify factors affectimg the production of wetland rice in the Sidondo 1 village,SigiBiromarusub-district of Sigiregency and to determine the level of the income of the wetland rice farming. This research was carried out in April to June 2013 in the Sidondo 1 village,SigiBiromarusub-district ofSigiregency. Respondents were selected using a simple random sampling method.Thirty respondents were taken among100 wetland rice. Data was analyzed using the Cobb-Douglas function and income analysis.  Land area, seeds, fertilizers, labors significantly affected the wetland rice production.  The income of the farmers wasIDR 34,191,323.13/1.73 ha/planting season with an average land area of 1.73 ha or IDR 19,725,263.35 ha/planting season.Key words : Income, Farm, Rice Farming, Production